PENGARUH FAKTOR INTERNAL DAN EKSTERNAL BANK TERHADAP KINERJA KEUANGAN PADA BANK UMUM DI INDONESIA - Lestari, Henny Setyo; Aprilriani, Giya (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT Research aims to determine the influence of significant internal and external factors that affect the performance of bank commercial bank in Indonesia. This research is use purposive sampling method to classify the company that will be sample analysis 20 banks was passed some criteria to be the samples of this research. The statistical method used is multiple regression with eviews 9. The dependent variable used is Return On Equity (ROE) and Economic Value Added (EVA). Independent variables used are Capital Adequacy Ratio (CAR), Asset Quality (ASQ), Deposits (TDTA), Efficiency (EFF), Operating efficiency (OPEFF), Inflation (INF) and Gross Domestic Product (GDP). The results show that there is a negatif influence between Capital Adequacy Ratio on theÃ‚Â  Return On Equity. And there is a positive influence between Economic Growth on the Return On Equity. Asset Quality, Deposits, Efficiency, Operating efficiency, Inflasi insignificant on the Return On Equity. Asset Quality have a positive influence on the Economic Value Added (EVA). And Operating efficiency have a negative influence on the Economic Value Added. Capital Adequacy Ratio, Deposits, Efficiency, Inflasi dan Economic Growth insignificant on the Economic Value Added. Keywords: asset quality, capital adequacy ratio, deposits, efficiency, inflasi, operating efficiency, economic growth